2013
DOI: 10.1007/s00285-013-0731-1
|View full text |Cite
|
Sign up to set email alerts
|

Flux modules in metabolic networks

Abstract: The huge number of elementary flux modes in genome-scale metabolic networks makes analysis based on elementary flux modes intrinsically difficult. However, it has been shown that the elementary flux modes with optimal yield often contain highly redundant information. The set of optimal-yield elementary flux modes can be compressed using modules. Up to now, this compression was only possible by first enumerating the whole set of all optimal-yield elementary flux modes. We present a direct method for computing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Similarly, υ A is the subvector of υ with only entries corresponding to reactions in A. With this definition, originally introduced by Müller and Bockmayr [11], the flux modules can be efficiently computed [12]. By computing the pathways through each module, a comprehensive pathway-based description can be obtained efficiently [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, υ A is the subvector of υ with only entries corresponding to reactions in A. With this definition, originally introduced by Müller and Bockmayr [11], the flux modules can be efficiently computed [12]. By computing the pathways through each module, a comprehensive pathway-based description can be obtained efficiently [13].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we also allow b = 0 to simplify notation in the context of modules. Furthermore, the space of optimal-yield fluxes is again a polyhedron and can be written in this form, too [15]. In this paper we will show that we can reduce the analysis of P to the analysis of linear vector spaces, i.e.…”
Section: Definitions and Preliminariesmentioning
confidence: 99%
“…Each such a module has in each optimum specific fixed input and output compounds. Müller and Bockmayr [15] used this property to formalize the notion of flux-module in a mathematically rigorous way. This allowed them to show that every optimal yield elementary flux mode (EFM) [23] is a concatenation of reactions with fixed flux and an elementary mode of each of the flux modules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that flux modules [9,15] of genome-scale metabolic networks can efficiently be computed using matroids. We confirmed the previous results that the optimal flux space of most genome-scale metabolic networks decomposes into modules.…”
Section: Enumeration Of Optimal-yield Pathwaysmentioning
confidence: 99%